Influence of carbonization conditions on the pyrolytic carbon deposition in acacia and eucalyptus wood chars - Kumar M.; Gupta R.C. (My University, 2025)
The amount of deposited pyrolytic carbon (resulting from the cracking of volatile matter) was found to depend on wood species and carbonization conditions, such as temperature and heating rate. Maximum pyrolytic carbon deposition in both the acacia and eucalyptus wood chars has been observed at a carbonization temperature of 8000°C. Rapid carbonization (higher heating rate) of wood significantly reduces the amount of deposited pyrolytic carbon in resulting chars. Results also indicate that the amount of deposited pyrolytic carbon in acacia wood char a less than that in eucalyptus wood char.